Neuropsychological, neuroimage and psychiatric aspects of primary Sjögren's syndrome - Gilberto N.O. Brito; Gloria R.B. Araujo; J. Angelo Papi (Arquivos de Neuro-Psiquiatria)
We report a case of a 49-year-old woman diagnosed with primary Sjögrens Syndrome (pSS) who was submitted to extensive neuropsychobiological assessment. Examination revealed a Wechsler Adult Intelligence Scale-Revised (WAIS-R) Full Scale IQ of 97 with no Verbal/Performance IQ discrepancy and performance below estimated premorbid levels on arithmetic skills, visual tracking, naming and delayed paired associate learning/memory. CT scans of the brain were normal. However, there were subcortical hyperintensities on MRI and left parieto-temporal hypoperfusion on SPECT. Neuropsychological impairment is consistent with the pattern of neuroimage findings. We hypothesize that the pathophysiological mechanisms of pSS involve direct immune attack on neurons in addition to indirect effects through small-vessel angiopathy and thereby induce natural fracture lines in behavior according to location in the central nervous system.